A Sialylated Glycan Microarray Reveals Novel Interactions of Modified Sialic Acids with Proteins and Viruses - Song, Xuezheng (American Society for Biochemistry and Molecular Biology, 2011)
Many glycan-binding proteins in animals and pathogens recognize sialic acid or its modified forms, but their molecular recognition is poorly understood. Here we describe studies on sialic acid recognition using a novel sialylated glycan microarray containing modified sialic acids presented on different glycan backbones. Glycans terminating in β-linked galactose at the non-reducing end and with an alkylamine-containing fluorophore at the reducing end were sialylated by a one-pot three-enzyme system to generate α2–3- and α2–6-linked sialyl glycans with 16 modified sialic acids. The resulting 77 sialyl glycans were purified and quantified, characterized by mass spectrometry, covalently printed on activated slides, and interrogated with a number of key sialic acid-binding proteins and viruses. Sialic acid recognition by the sialic acid-binding lectins Sambucus nigra agglutinin and Maackia amurensis lectin-I, which are routinely used for detecting α2–6- and α2–3-linked sialic acids, are affected by sialic acid modifications, and both lectins bind glycans terminating with 2-keto-3-deoxy-d-glycero-d-galactonononic acid (Kdn) and Kdn derivatives stronger than the derivatives of more common N-acetylneuraminic acid (Neu5Ac) and N-glycolylneuraminic acid (Neu5Gc). Three human parainfluenza viruses bind to glycans terminating with Neu5Ac or Neu5Gc and some of their derivatives but not to Kdn and its derivatives. Influenza A virus also does not bind glycans terminating in Kdn or Kdn derivatives. An especially novel aspect of human influenza A virus binding is its ability to equivalently recognize glycans terminated with either α2–6-linked Neu5Ac9Lt or α2–6-linked Neu5Ac. Our results demonstrate the utility of this sialylated glycan microarray to investigate the biological importance of modified sialic acids in protein-glycan interactions.